Carbon pricing – perceived strengths, weaknesses and knowledge gaps according to a global expert survey - Ivan Savin; Stefan Drews; Jeroen van den Bergh (Environmental Research Letters, 2024)
Researchers from different disciplines have different opinions about carbon pricing. To better understand the reasoning behind these perspectives, we utilize responses to three open-ended questions from a global survey among almost 800 researchers from a wide variety of fields who published on climate policy. Using methods from computational linguistics, we classify reflections of researchers on the main strengths and weaknesses of carbon pricing compared with other policy instruments in seven and six topics, respectively. The results indicate that the main perceived strengths of carbon pricing are that it is effective and efficient at reducing emissions, gives clear investment incentives, decentralizes policy, among others. The main perceived weaknesses of carbon pricing are related to its potentially regressive effects on households, low social-political support, and amenability to manipulation—to name a few. Surprisingly, not all these perceptions are in line with established theory and empirical evidence. Finally, we collect suggestions for future research. Among nine frequently mentioned themes are improving public understanding of carbon pricing, political acceptability, synergies with other policies, long-term effects, and implementation in an equitable way in developing countries and worldwide. In addition, we highlight several less frequent but arguably innovative research avenues. Finally, we report to what extent the identified topics on strengths, weaknesses and knowledge gaps are significantly related to academic experience, gender, GDP per capita in the countries of origin and residence of the survey participants, and perceived importance of carbon pricing. This information helps identifying key differences in views within the scientific community on carbon pricing and can guide communication between fields aimed at reaching more consensus on climate policy.